2014
DOI: 10.3233/jad-132348
|View full text |Cite
|
Sign up to set email alerts
|

Examining Executive Dysfunction with the Institute of Cognitive Neurology (INECO) Frontal Screening (IFS): Normative Values from a Healthy Sample and Clinical Utility in Alzheimer's Disease

Abstract: Age and education should be taken into account when interpreting performance on the IFS. The IFS is useful to detect executive dysfunction in AD, showing good discriminant and concurrent validities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 81 publications
(130 reference statements)
3
35
0
2
Order By: Relevance
“…Comparisons between IFS and FAB were undertaken, and these have shown that IFS is more sensitive and specific in differentiating bvFTD from AD (Gleichgerrcht et al, 2011 ; Custodio et al, 2016 ), and it also correlates more strongly with standard executive tasks (e.g., TMT-B, WCST, Gleichgerrcht et al, 2011 ). Nonetheless, the advantage of IFS over FAB remains to be established: in a study with AD patients, they showed similar diagnostic accuracy (0.88 and 0.87, respectively) and similar correlations with other measures of EF (Moreira et al, 2014 ). IFS scores also correlate with MMSE scores (Torralva et al, 2009 ; Ihnen et al, 2013 ; Moreira et al, 2014 ) and are influenced by age (Moreira et al, 2014 ) and education (Ihnen et al, 2013 ; Moreira et al, 2014 ), reinforcing the need of normative data to take these variables into account.…”
Section: Screening Tools Of Executive Functionsmentioning
confidence: 92%
See 3 more Smart Citations
“…Comparisons between IFS and FAB were undertaken, and these have shown that IFS is more sensitive and specific in differentiating bvFTD from AD (Gleichgerrcht et al, 2011 ; Custodio et al, 2016 ), and it also correlates more strongly with standard executive tasks (e.g., TMT-B, WCST, Gleichgerrcht et al, 2011 ). Nonetheless, the advantage of IFS over FAB remains to be established: in a study with AD patients, they showed similar diagnostic accuracy (0.88 and 0.87, respectively) and similar correlations with other measures of EF (Moreira et al, 2014 ). IFS scores also correlate with MMSE scores (Torralva et al, 2009 ; Ihnen et al, 2013 ; Moreira et al, 2014 ) and are influenced by age (Moreira et al, 2014 ) and education (Ihnen et al, 2013 ; Moreira et al, 2014 ), reinforcing the need of normative data to take these variables into account.…”
Section: Screening Tools Of Executive Functionsmentioning
confidence: 92%
“…Concerning byFTD and AD patients, although bvFTD presented lower scores in some studies (Iavarone et al, 2004 ; Slachevsky et al, 2004 ; Nakaaki et al, 2007 ), in other studies differences were not significant (Castiglioni et al, 2006 ; Gleichgerrcht et al, 2011 ). Additionally, some of its subtests have been shown to have poor sensitivity (e.g., Prehension Behaviour and Letter Fluency; Lima et al, 2008 ; Moreira et al, 2014 ). Age (Iavarone et al, 2004 ; Appollonio et al, 2005 ; Lima et al, 2008 ) and education (Iavarone et al, 2004 ; Appollonio et al, 2005 ; Rodrigues et al, 2009 ) should be considered when interpreting FAB scores, since they are predictors of performance, with advanced age and less years of education predicting lower scores.…”
Section: Screening Tools Of Executive Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…While brief executive screening tests have been developed to address this issue, many existing tools were not specifically designed for use within dementia populations,14 show limited discrimination between bvFTD and AD,15 include items that are vulnerable to misinterpretation16 or items which fail to exclusively tap executive functions 17. Tools focusing on executive function to assist with differential dementia diagnosis already exist (eg, INECO Frontal Screen;18 Frontal Assessment Battery19), but these are not without limitations, which include inconsistent patient differentiation across subtests,20 need for training in scoring responses and inclusion of items vulnerable to educational achievement 21. While the Addenbrooke's Cognitive Examination,22 a broad cognitive screening tool, is also often thought to assist with differential diagnosis, this was not its intended design and an acknowledged caveat of the test is its limited capacity to assess executive functions.…”
Section: Introductionmentioning
confidence: 99%